Silica granules for thermal treatment
The silica pellets prepared by the gas phase method are optimized by flame hydrolysis or flame oxidation method, and the particle size distribution and pore volume are solved in the prior art. The problem of low performance and blockage of silica pellets at high temperatures in the existing technology is solved, and the problem of low performance and blockage of silica pellets at high temperatures is achieved. High bulk density and mechanical strength, suitable for continuous heat treatment, and improves sintering performance and throughput.
Patent Information
- Application Number
- CN202180037792.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-25
- Filing Date
- 2021-05-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-05-14
AI Technical Summary
The method used in the prior art for preparing heat-treated silica pellets has problems of low performance, blockage and poor product properties, especially when continuous heat treatment is carried out at high temperatures, the bulk density and porosity of silica pellets. Difficult to optimize effectively.
The vapor phase silica pellets are prepared by flame hydrolysis or flame oxidation method to control the particle size distribution, pore volume and surface area, ensure the high bulk density and mechanical strength of the pellets, and are suitable for continuous heat treatment methods to avoid clogging.
Silica pellets with high bulk density and mechanical strength are suitable for continuous heat treatment, which improves sintering performance and throughput, avoids blockage of heat treatment devices, and improves product quality and production efficiency.
Smart Images

Figure BDA0003960983780000131
Abstract
Description
[0001] The invention relates to fumed silicon dioxide granules for preparing heat-treated silicon dioxide granules, and to the preparation and use thereof.
[0002] Granules based on fumed silica can be used in a wide variety of applications, for example as catalyst supports, carriers for liquid substances, for cosmetic applications, for thermal insulation, as pharmaceutical excipients, etc.
[0003] For certain applications, such as for the preparation of catalyst supports or grinding materials, the silica granules need to be subjected to a heat treatment step. During this step, which is typically carried out at temperatures above 300° C. to 500° C., all volatile residues are eliminated and the number of free silanol groups on the silica surface and the overall porosity are significantly reduced. Such heat-treated silica granules generally possess a higher bulk density than their precursors. Typically, undesirable agglomerations often form larger silica fragments and blockages occur during the heat treatment step.
[0004] Many methods are known for preparing fumed silica granules from fumed silica powder dioxide, which can be used as a precursor for a subsequent thermal treatment. Such preparation generally involves agglomeration of the fumed silica particles. This can be accomplished by means of wet granulation. In wet granulation, an aqueous colloidal fumed silica dispersion is generally prepared under constant mixing. The solvent is then gradually removed to leave a dry residue, which can be further comminuted and classified.
[0005] US20170008772A1 describes the preparation of synthetic amorphous silica powder by a method comprising the following steps: (a) forming and then drying a fumed silica slurry, for example in a rotary kiln, to obtain silica powder; (b) calcining the obtained silica powder at 900°C to 1200°C; (c) pulverizing and calcining at 1100°C to 1400°C; (d) pulverizing and washing; (e) filtering to obtain the target sintered silica powder. The non-sintered silica granules obtained by evaporating water from the silica slurry in step (a) of the method are not mechanically compacted, thereby having a relatively high porosity and a low bulk density. In contrast, the sintered silica particles obtained after step (b) of the method have almost no porosity and have a very low BET surface area.
[0006] US 4042361 discloses a method for preparing silica granules, in which pyrogenic silica is used. This is added to water to form a dispersion, the water is then evaporated under heating, the residue is crushed into pieces of a size ranging from about one millimeter to several centimeters, which are further calcined at 1150°C to 1500°C.
[0007] A special type of wet granulation process is based on spray drying of silicon dioxide dispersions to obtain spherical granules with a narrow particle size distribution.
[0008] EP 1717202 A1 discloses the preparation of a sintered material based on silicon dioxide having an average particle size of 10 to 120 μm, which involves the steps of spray drying a dispersion comprising fumed silicon dioxide and subsequent heat treatment of the silicon dioxide granules.
[0009] Silica granules can also be obtained by dry compacting silica. Compacting dry fumed silica is difficult because fumed silica is very dry and there are no capillary forces to achieve particle bonding. Fumed silica is characterized by extreme fineness, low bulk density, high surface area, very high purity, essentially spherical primary particle shape and no pores. Fumed silica often has a high surface charge, which complicates agglomeration due to electrostatic interactions.
[0010] WO 2009007180 A1 discloses a method for preparing a 2 A method for producing silica granules having a BET surface area of 100 μm and a median particle size of 10 to 140 μm, wherein the silica granules can be prepared by: (a) compacting fumed silica powder into blocks; (b) crushing the blocks and removing block fragments of <100 μm and >800 μm; (c) treating the resulting block fragments having a tamped density of 300 g / L to 600 g / L at 600° C. to 1100° C. in an atmosphere suitable for removing hydroxyl groups; and (d) sintering at 1200° C. to 1400° C.
[0011] US 20160082415 A1 relates to providing a functionalized silica support material with improved desorption characteristics (e.g., adsorption of enzymes). US 20160082415 A1 discloses a method for preparing such functionalized granular silica, which comprises shaping precipitated silica or fumed silica by dry compaction to give a block, sieve granulating it or sieving it at a sieve size of 3000 μm, sieving out fine powder, and then reacting the obtained granules with a surface modifier. Only specific examples of precipitated silica granules are given in this patent application.
[0012] US 20190053150 A1 and US 20190062193 A1 both disclose a method for preparing fumed silica granules by spray drying an aqueous dispersion and subsequently melting the silica granules, wherein the fumed silica granules have a pore volume of 0.1 to 2.5 mL / g and a bulk density of 0.5 to 1.2 g / cm 3 , average particle size d 50 In the range of 150 to 300 μm.
[0013] The selection of an appropriate silica precursor for preparing the heat-treated silica article is of utmost importance. Many types of silica granules known from the prior art are not best suited for such a heat treatment process, which results in a heat-treated silica product having lower performance, clogging, and poor product properties.
[0014] It is an object of the present invention to provide a granular silicon dioxide-based material which is optimized for the preparation of heat-treated silicon dioxide granules having an increased bulk density, in particular by a continuous process.
[0015] Such silica-based granular materials should be suitable for continuous thermal processing in a rotary kiln or similar apparatus with high throughput and without clogging.
[0016] Fumed silica pellets
[0017] The present invention provides fumed silica granules, which:
[0018] BET surface area is 20 m 2 / g to 500m 2 / g;
[0019] Number average particle size d 50 350μm to 2000μm, measured by laser diffraction;
[0020] The span of particle size distribution (d 90 -d 10 ) / d 50 0.8 to 3.0, measured by laser diffraction;
[0021] Bulk density greater than 0.35 g / mL, determined by mercury intrusion;
[0022] The pore volume of pores >4 nm does not exceed 1.5 cm 3 / g, determined by mercury intrusion porosimetry.
[0023] In the context of the present invention, the terms "granular material", "granulate" and "granules" are used interchangeably and refer to granular, easily pourable, free-flowing particulate solid material. The granules of the present invention may be spherical or any other shaped particles, such as pellets, rings, etc., or irregularly shaped fragments of any crushed shaped body, for example, having a statistical particle size distribution.
[0024] The granules of the present invention are made of fumed silica. Fumed silica can be prepared by flame hydrolysis or flame oxidation. This involves oxidation or hydrolysis of hydrolyzable or oxidizable starting materials, usually in a hydrogen / oxygen flame. Starting materials for pyrolysis methods include organic and inorganic substances. Silicon tetrachloride is particularly suitable. The hydrophilic silica obtained is amorphous. Fumed silica is usually in aggregated form. "Aggregated" means that the so-called primary particles formed first later become firmly bound to each other in the reaction to form a three-dimensional network. The primary particles are essentially free of pores and have free hydroxyl groups on their surfaces.
[0025] The granules according to the invention consist essentially of fumed silica, i.e. contain at least 85% by weight, preferably at least 90% by weight, more preferably 95% to 100% by weight of fumed silica. In addition to fumed silica, the granules may also contain water and some minor impurities.
[0026] The sum of metal impurities in the pellets of the present invention is preferably less than 500 ppm, more preferably less than 200 ppm, more preferably less than 100 ppm, and more preferably less than 50 ppm.
[0027] Secondary impurities may include Ca, Cu, K, Li, Mg, Mn, Na, Ti, V, Zr, Al, B, Cr, Ni, P. To determine the metal content, the silicon dioxide pellets are dissolved in a solution containing hydrofluoric acid. The silicon tetrafluoride formed as the evaporant and the remaining residue are analyzed by inductively coupled plasma mass spectrometry (ICP-MS).
[0028] The particle size distribution of the granules of the present invention can have a substantial impact on the suitability of such silica granules for use in processes involving thermal treatment.
[0029] The number average particle size d of the granules according to the invention is 50 The particle size distribution of the granules is preferably 350 μm to 2000 μm, preferably 350 μm to 1800 μm, more preferably 350 μm to 1600 μm, more preferably 400 μm to 1400 μm, more preferably 400 μm to 1200 μm, more preferably 500 μm to 1150 μm, more preferably 550 μm to 1100 μm, even more preferably 600 μm to 1050 μm, and most preferably 700 μm to 1000 μm. The number average particle size of the granules can be determined by laser diffraction particle size analysis according to ISO 13320:2009. The average particle size distribution obtained by the measurement is converted into the average value d 50 (which means that 50% of all particles do not exceed this particle size) is defined as the number average particle size.
[0030] The d of the granules according to the invention 10The value is preferably 100 μm to 1000 μm, more preferably 120 μm to 900 μm, more preferably 150 μm to 850 μm, more preferably 200 μm to 800 μm, more preferably 250 μm to 750 μm, more preferably 300 μm to 700 μm. 90 The value of d is 800 μm to 2500 μm, more preferably 900 μm to 2000 μm, more preferably 950 μm to 1900 μm, and more preferably 1000 μm to 1800 μm. The d can be determined by laser diffraction particle size analysis according to ISO 13320:2009. 10 Value and d 90 The particle size distribution obtained by the measurement is defined as 10 Value and d 90 Value, which means that 10% or 90% of all particles do not exceed this particle size.
[0031] The granules of the present invention preferably have a particle size of not more than 2000 μm, more preferably not more than 1700 μm, more preferably not more than 1500 μm, more preferably not more than 1300 μm. The absence of particles exceeding the particle size range can be achieved, for example, by sieving the granules through an appropriate sieve.
[0032] The ratio of particles having a particle size of not more than 100 μm in the granules of the present invention is preferably less than 30% by weight, more preferably less than 20% by weight, more preferably less than 15% by weight, more preferably less than 10% by weight. This ratio can be calculated from the results of particle size analysis by laser diffraction.
[0033] The pellets of the present invention have a relatively narrow particle size distribution, which can be characterized by the span (d 90 -d 10 ) / d 50 The particle size distribution of the silica granules of the present invention is 0.8 to 3.0, preferably 0.9 to 2.0, more preferably 1.0 to 1.8, more preferably 1.1 to 1.7, and more preferably 1.2 to 1.6. It has been found that granules with such a narrow particle size distribution can be particularly suitable for heat treatment in a continuous manner. The narrow particle size distribution of the silica granules of the present invention is due to the presence of a relatively low ratio of fines to larger silica granules. Silica fines may cause blockages during a continuous heat treatment process. Larger silica granules may be mechanically unstable during a continuous heat treatment process, for example in a rotary kiln, and may deagglomerate to form fines.
[0034] The term "pore volume of pores >4 nm" refers to the cumulative pore volume of pores >4 nm, which can be determined by mercury intrusion porosimetry according to DIN ISO 15901-1. The principle of this method was first described by HL Ritter and LC Drake in Ind. Eng. Chem. Anal. Ed. 17 (1945) pp. 782-786 and pp 787-791, and measures the volume of mercury pressed into a porous solid based on the applied pressure. Only pores into which mercury can penetrate at the maximum applied pressure (e.g. 417 MPa), i.e. pores with a pore size of generally >4 nm, are detected. Liquid mercury does not wet the surface of the probe porous solid and penetrates into the pores only under pressure. The pressure to be applied is inversely proportional to the opening width of the pore. In the case of cylindrical pores, the Washburn equation gives the pore radius r p Relationship with pressure p:
[0035] r p =-(2×σ / p)×cosθ
[0036] in:
[0037] r p is the hole radius
[0038] p is pressure
[0039] σ is the surface tension of mercury (0.48 N / m)
[0040] θ is the contact angle of mercury (140°C)
[0041] The pore volume of pores >4 nm corresponds to the cumulative pore volume of all pores which can be determined by mercury intrusion porosimetry in accordance with DIN ISO 15901-1 up to a maximum pressure of 417 MPa.
[0042] The pore volume of pores >4 nm of the granules according to the invention, determined by mercury porosimetry according to DIN ISO 15901-1, does not exceed 1.5 cm 3 / g, preferably 0.1cm 3 / g to 1.5cm 3 / g, more preferably 0.2 cm 3 / g to 1.45cm 3 / g, more preferably 0.3 cm 3 / g to 1.4cm 3 / g, more preferably 0.5cm 3 / g to 1.3cm 3 / g, more preferably 0.6cm 3 / g to 1.2cm 3 / g, more preferably 0.7 cm 3 / g to 1.1cm3 / g, more preferably 0.8cm 3 / g to 1.0cm 3 / g.
[0043] The term “pore volume of pores <4 μm” means the cumulative pore volume of pores <4 μm which can be determined by mercury porosimetry to DIN ISO 15901-1 and corresponds to the cumulative pore volume of all pores <4 μm which can be determined by this method.
[0044] The pore volume of pores <4 μm of the granules according to the invention, determined by mercury porosimetry according to DIN ISO 15901-1, is preferably less than 1.4 cm 3 / g, more preferably 0.05cm 3 / g to 1.4cm 3 / g, more preferably 0.1cm 3 / g to 1.3cm 3 / g, more preferably 0.2 cm 3 / g to 1.25cm 3 / g, more preferably 0.3 cm 3 / g to 1.2cm 3 / g, more preferably 0.4cm 3 / g to 1.2cm 3 / g, more preferably 0.4cm 3 / g to 1.1cm 3 / g, more preferably 0.4cm 3 / g to 1.0cm 3 / g, more preferably 0.4cm 3 / g to 0.9cm 3 / g, more preferably 0.5cm 3 / g to 0.9cm 3 / g, more preferably 0.6cm 3 / g to 0.9cm 3 / g.
[0045] The pore volume is determined by mercury intrusion porosimetry according to DIN ISO 15901-1, and the percentage of the pore volume of pores <4 μm to the cumulative pore volume of pores >4 nm of the granules according to the invention is preferably greater than 35%, more preferably greater than 40%, more preferably greater than 50%, more preferably from 55% to 95%, more preferably from 60% to 90%, more preferably from 65% to 85%, more preferably from 70% to 80%. The percentage of the pore volume of pores <4 μm to the cumulative pore volume of pores >4 nm can be obtained by dividing the pore volume of the former by the pore volume of the latter and multiplying the result by 100%.
[0046] The porosity of the particle size determined by mercury intrusion porosimetry according to DIN ISO 15901-1 is preferably less than 77%, more preferably 10 to 75%, more preferably 20 to 70%, more preferably 30 to 75%, more preferably 40 to 72%, more preferably 50 to 70%, more preferably 52 to 67%, more preferably 55 to 65%.
[0047] The granules according to the invention are characterized by limited porosity and pore volume as measured by mercury intrusion when compared to similar silica materials known in the prior art. Without wishing to be bound by any theory, it is believed that such reduced porosity is related to the lower rate of water evaporation and removal of free silanol groups from the silica surface under thermal treatment. Therefore, if the porosity and pore volume are too high, when rapid sintering of the thermally treated silica granules occurs, blockages may result during the sintering process and reduced performance.
[0048] The BET surface area of the pellets of the present invention is 20 m 2 / g to 500m 2 / g, preferably 30m 2 / g to 450m 2 / g, more preferably 40m 2 / g to 400m 2 / g, more preferably 50m 2 / g to 380m 2 / g, more preferably 60m 2 / g to 350m 2 / g, more preferably 70m 2 / g to 320m 2 / g, more preferably 80m 2 / g to 320m 2 / g, more preferably 80m 2 / g to 220m 2 The specific surface area (also referred to as BET surface area for short) can be determined in accordance with DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller method.
[0049] The tamped density of the pellets according to the present invention is preferably greater than 200 g / L, more preferably 200 g / L to 1000 g / L, more preferably 230 g / L to 800 g / L, more preferably 250 g / L to 700 g / L, more preferably 280 g / L to 650 g / L, more preferably 300 g / L to 600 g / L, more preferably 320 g / L to 550 g / L.
[0050] The tamped density of various powdery or coarse-grained granular materials can be determined according to DIN ISO 787-11:1995 "General methods of test for pigments and extenders--Part 11: Determination of tamped volume and apparent density after tamping". This involves measuring the apparent density of the bed after agitation and tamping.
[0051] The bulk density of the granules according to the invention, determined by mercury intrusion, is greater than 0.35 g / mL, more preferably 0.35 g / mL to 1.20 g / mL, more preferably 0.40 g / mL to 1.1 g / mL, more preferably 0.45 g / mL to 1.0 g / mL, more preferably 0.47 g / mL to 0.95 g / mL, more preferably 0.50 g / mL to 0.90 g / mL, more preferably 0.55 g / mL to 0.85 g / mL, more preferably 0.60 g / mL to 0.80 g / mL. The bulk density of the granules according to the invention can be determined by mercury intrusion according to DIN ISO 15901-1 at a minimum mercury pressure applied in the process, for example at a pressure of <0.01 MPa (e.g. 0.0031 MPa).
[0052] The bulk density determined by mercury intrusion porosimetry is considered to be a more appropriate value for defining the material density of a granular material than, for example, the tamped density of the same material. Thus, the bulk density determined by mercury intrusion porosimetry does not include the large spaces between the particles, into which mercury can penetrate at minimal applied pressure, whereas the tamped density defines the material density including all spaces between the particles.
[0053] The relatively high bulk density of the granules of the invention is associated with their increased mechanical strength, which is very beneficial for further handling or further processing, especially thermal treatment of such silica material. If such thermal treatment is carried out in a continuous manner, for example in a rotary kiln or similar apparatus, the increased mechanical strength of the silica granules inhibits the formation of unwanted fines and clogging during the process.
[0054] Method for preparing pellets
[0055] The present invention further provides a method for preparing the pellets of the present invention, comprising the following steps:
[0056] a) compacting fumed silica having a water content of 0.1% to 10% by weight to obtain compacted silica fragments having a tamped density of at least 200 g / L;
[0057] b) crushing the compacted silicon dioxide fragments obtained in step a) using a sieve having a maximum mesh size of 1000 μm to 2000 μm, while separating crushed fragments having a size of not more than 2000 μm;
[0058] c) separating fine particles from the crushed fragments having a size of not more than 2000 μm obtained in step b) using a sieve having a maximum mesh size of 200 μm to 600 μm to obtain the granules;
[0059] d) optionally using the fine particles separated in step c) having a particle size of not more than 600 μm in step a).
[0060] The method of the present invention preferably comprises all steps a) to d). In this case, the silica fine powder having a particle size of not more than 600 μm, more preferably not more than 500 μm, more preferably not more than 400 μm separated in step c) can be mixed with fresh fumed silica and reused in step a) of the method. This reduces the amount of wasted silica material and improves the overall yield of the method.
[0061] Steps a) to d) of the method according to the invention are preferably performed sequentially, ie step a) is followed by step b), then c) and finally step d).
[0062] The process of the present invention can be carried out batchwise, semi-continuously or, preferably, continuously.
[0063] In step a) of the method of the present invention, the number average particle size d 50 The fumed silica has a particle size of not more than 600 μm, preferably 5 to 500 μm, more preferably 10 to 400 μm, more preferably 15 to 300 μm, and more preferably 20 to 200 μm. The number average particle size d of the fumed silica is 50 It can be measured by laser diffraction particle size analysis according to ISO 13320:2009.
[0064] In step a) of the method, a fumed silica having a water content of 0.1% to 10% by weight, preferably 0.3% to 8.0% by weight, more preferably 0.5% to 5.0% by weight, more preferably 1.0% to 3.0% by weight is used as a starting material for preparing silica granules. Surprisingly, it has been found that the water content of this selected fumed silica can prepare silica granules with improved mechanical properties and higher productivity. In order to achieve the required water content of the fumed silica, water can be added before or during step a) of the method of the present invention using any appropriate technology or device. Water can be sprayed onto the fumed silica, for example, to achieve its uniform distribution.
[0065] The fumed silica used in step a) of the method of the present invention may have a tamped density of 15 to 190 g / L, preferably 20 to 150 g / L, more preferably 30 to 100 g / L, and more preferably 40 to 80 g / L.
[0066] In step a), the fumed silica is compacted to obtain compacted silica flakes having a tamped density of at least 200 g / L, preferably 200 g / L to 1000 g / L, more preferably 230 g / L to 800 g / L, more preferably 250 g / L to 700 g / L, more preferably 280 g / L to 650 g / L, more preferably 300 g / L to 600 g / L, more preferably 320 g / L to 550 g / L. The tamped density of the fumed silica and the tamped density of the compacted silica flakes can be determined according to DIN ISO 787-11:1995.
[0067] The relatively high tamping density of the compacted fragments obtained in step a) of the process according to the invention leads to a higher mechanical strength, less formation of fines and, in the subsequent thermal treatment of such silica granules, finally to higher sintering properties of the silica granules.
[0068] Compacting in step a) of the method refers to mechanical compression, preferably without the addition of any binder. Compacting should ensure uniform compression of the fumed silica powder to obtain compacted silica fragments having substantially equal tamped density.
[0069] Step a) of the method of the present invention can be achieved by any suitable means, for example by compacting the fumed silica in a roller press to obtain compacted silica fragments in the form of a strip intermediate. The properties of such compacted silica fragments can be influenced by process parameters such as the selected process control mode, the compaction force, the gap width between the two rollers, and the pressure holding time determined by appropriately changing the rotation speed of the pressing rollers.
[0070] The compaction of the compacted silicon dioxide flakes can be achieved by means of two rollers, one or both of which can simultaneously have a degassing function.
[0071] Preferably, two compacting rollers can be used, which can be smooth or profiled. The profile can be present on only one compacting roller or on both compacting rollers. The profile can consist of parallel waveforms in the axial direction or of any arrangement of recesses (depressions) of any configuration. In another embodiment of the invention, at least one of the rollers can be a vacuum roller press.
[0072] For the compaction in step a) of the method according to the invention, a suitable method is in particular a method in which the fumed silica to be compacted is compacted by means of two pressing rollers. One of the rollers may be arranged to be rotatably driven. Alternatively, the two compacting rollers may also be non-drivable. The specific pressure applied between the two compacting rollers may be 5 kN / cm to 50 kN / cm, preferably greater than 12 kN / cm, more preferably greater than 12 kN / cm and less than 30 kN / cm, more preferably greater than 12 kN / cm and less than 18 kN / cm.
[0073] After compaction in step a) of the process, the compacted silica fragments obtained are crushed in step b) using a sieve having a maximum mesh size of 1000 to 2000 μm, preferably 1000 to 1500 μm, at separation of crushed fragments having a particle size of not more than 2000 μm, preferably not more than 1500 μm. Step b) of the process can be carried out using any suitable device having a sieve and capable of crushing silica fragments, for example in a screen granulator.
[0074] For crushing the compacted silica fragments in step b) of the process, an apparatus having two contra rotatory rollers or spiked rollers with a defined gap may be used.
[0075] In step c) of the method of the present invention, the crushed fragments with a particle size of less than 2000 μm separated in step b) are further separated by using a sieve with a mesh size of 200 μm to 600 μm, preferably 250 μm to 600 μm, more preferably 300 μm to 600 μm, more preferably 350 μm to 600 μm, more preferably 400 μm to 600 μm, to separate fine particles with a particle size of not more than 600 μm, preferably not more than 550 μm, more preferably not more than 500 μm.
[0076] The relatively small difference between the mesh sizes used in steps b) and c) of the process of the present invention results in the obtained silica granules having a narrow particle size distribution, which is particularly beneficial for improving the sintering performance of a continuous sintering process using such silica granules.
[0077] Step c) of the method of the present invention can be carried out by means of any suitable device having a sieve, such as a sifter, a screen or a classifier. The sieve used can be a crossflow sifters, a counter current deflection sifters, etc. The classifier used can be a cyclone separator.
[0078] The particles having a particle size of not more than 600 μm separated in step c) of the process according to the invention are optionally used in step a) of the process.
[0079] The method according to the present invention may additionally include an optional purification step e). In the step e) of the method, the pellets obtained in the step c) of the method are exposed to an atmosphere containing one or more reactive compounds suitable for removing hydroxyl groups and impurities at a temperature of 400° C. to 1100° C., preferably 600° C. to 900° C. These may preferably be chlorine (Cl ), hydrochloric acid (HCl), sulphur halides (sulphur halides) (e.g. SCl , S Cl , SCl ), and / or sulphur oxide halides (sulphur oxide halides) (e.g. SOCl , SO Cl ), hydrogen, or a mixture thereof. More preferably, chlorine, hydrochloric acid, disulfur dichloride or thionyl chloride may be used. Typically, the reactive compound is used as a gas mixture with air, oxygen, helium, nitrogen, argon and / or carbon dioxide. The proportion of the reactive compound in such a gas mixture may be from 0.5% by volume to 20% by volume.
[0080] Uses of pellets
[0081] The granules according to the invention can be used in a variety of different applications, for example as catalyst carrier, carrier for liquid substances, in cosmetic applications, for thermal insulation, as pharmaceutical excipient, as abrasive, as a component of silicone rubber, etc.
[0082] The granules of the invention are particularly suitable for preparing thermally treated silicon dioxide granules, especially in a continuous process.
[0083] Such heat treatment can be carried out in any suitable equipment, for example in a suitable rotary kiln. In order to prepare heat-treated pellets of particularly high purity, especially low metal content, potential contamination during the heat treatment step should be avoided. For this purpose, the material of the heat treatment device should therefore be selected.
[0084] The heat treatment is preferably carried out at at least 300°C, more preferably at least 500°C, more preferably at least 700°C, more preferably at least 900°C, more preferably at least 1000°C, more preferably at least 1100°C, more preferably at least 1200°C.
[0085] In some cases, it may be advantageous to carry out the heat treatment of the pellets according to the invention in several steps, for example two, three or more steps, with different, successively increasing temperatures being individually adjusted in each heat treatment step. Surprisingly, it has been found that the overall throughput of such a heat treatment method can be increased and that unnecessary blockages of the heat treatment apparatus do not occur. Preferably, the heat treatment of the pellets according to the invention is carried out at a first heat treatment temperature and then at least at a second heat treatment temperature, wherein the second heat treatment temperature is at least 10°C, preferably at least 20°C, more preferably at least 30°C, more preferably at least 40°C, more preferably at least 50°C higher than the first heat treatment temperature.
[0086] Particularly preferably, the granules according to the invention can be used as precursors for preparing heat-treated high-density silica granules, for example as catalyst supports, carrier forms for liquid substances; as components of cosmetic preparations, thermal insulation compositions, as pharmaceutical excipients, as abrasives, as components of silicone rubbers, etc. Example
[0087] The particle size (d) of the particles was measured in a dry state using a laser diffraction analyzer Beckman Coulter LS. 10 ,d 50 ,d 90 ).
[0088] The bulk density, porosity and cumulative pore volume of pores larger than 4 nm were determined by mercury intrusion porosimetry according to DIN ISO 15901-1 using an AutoPore V 9600 device (Micomeritics). Only the pores into which mercury can penetrate at the maximum applied pressure (417 MPa), i.e. pores with a pore diameter >4 nm, were measured.
[0089] BET specific surface area (m 2 / g) was determined in accordance with DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller method.
[0090] Preparation of silica pellets
[0091] Example 1 (according to the present invention)
[0092] Fumed silica powder 90(BET=90m 2 / g, manufacturer: Evonik ResourceEfficiency GmbH) is placed in a storage tank and treated with demineralized water in a mixing unit (target value 1.5 wt. % H2O). In this unit, the fine powder obtained by sieving in one of the following method steps is then added and homogenized. From there, the material flows into the hopper without feeding, that is, solely due to its mass, in which the filling screw rotates. The hopper is subjected to negative pressure from the outside. The hopper wall consists of sintered metal covered with cloth. When the material is discharged by vacuum, the filling screw conveys the fumed silica powder to the roller. Between the rollers with a corrugated profile (6 mm), the material is squeezed with a specific pressure of more than 12 kN / cm and less than 18 kN / cm. Due to the corrugated profile, compressed, compacted "rods" of fumed silica are formed. These rods are then crushed in a screen granulator. The mesh size in the screen granulator is 1250 μm. The size of the mesh in the screen granulator defines the upper grain size. The lower size is defined in the subsequent sieving.
[0093] The material crushed in the screen granulator is sieved in a screen with ultrasonic cleaning and the undersize is separated. The screen hole size is 500 μm. The fine powder is returned to the storage container by a vacuum circulation conveyor.
[0094] Comparative Example 1
[0095] The same procedure as in Example 1 was followed, but in the subsequent sieving a sieve with a mesh size of 100 μm was used instead of the sieve with a mesh size of 500 μm used in Example 1.
[0096] Comparative Example 2
[0097] By spray drying technology (atomization with nozzle, dispersion pressure: 8 bar) from a 20 wt.% The silica granules were prepared from a 90% aqueous dispersion with a spray dryer inlet temperature of 350°C and an outlet temperature of 100°C. Drying was carried out in countercurrent mode. The product was post-treated in a fluidized bed to further increase the agglomerate size. The final product was separated with a filter.
[0098] The physicochemical properties of the silica granules of Example 1 and Comparative Examples 1 and 2 are summarized in Table 1.
[0099] Thermal treatment of silica pellets
[0100] The silicon dioxide granules of Example 1 and Comparative Examples 1 and 2 were continuously heat treated under identical conditions (maximum temperature = 1350° C.) in a rotary kiln having a diameter of about 140 mm and a length of 2 m. In each case, the feed rate of the silicon dioxide granules was continuously increased until the first signs of overloading and blocking appeared. Therefore, the maximum sintering performance (in kg / h) was determined and compared for the different granules (Table 1).
[0101] Compared to the silica from Comparative Examples 1 and 2, the silica pellets prepared in Example 1 had a much higher maximum throughput rate without any blockage (Table 1).
[0102] All three pellets have similar BET surface areas. Due to its preparation method, the pellets of Example 1 have a higher average particle size, higher bulk density, lower porosity and pore volume of pores > 4 nm than the other pellets (Table 1).
[0103] The silica granules from Comparative Example 2 have much higher fluidity (data not shown in Table 1) and a narrower particle size distribution than the granules from Example 1. However, the silica granules from Example 1 achieve higher maximum sintering performance, which cannot be explained simply by the particle shape or size, but by the particularly suitable combination of relatively large average particle size, relatively low porosity and high bulk density of such granules.
[0104] Table 1. Properties of silica pellets
[0105]
Claims
1. Fumed silica granules, BET surface area is 20 m 2 / g to 500m 2 / g; Number average particle size d 50 350μm to 2000μm, measured by laser diffraction; The span of particle size distribution (d 90 -d 10 ) / d 50 0.8 to 3.0, measured by laser diffraction; Bulk density greater than 0.35 g / mL, determined by mercury intrusion porosimetry; The pore volume of pores >4 nm does not exceed 1.5 cm 3 / g, determined by mercury intrusion porosimetry.
2. The pellet according to claim 1, wherein the pellet has a d 10 100μm to 1000μm, measured by laser diffraction. 3 . The pellet according to claim 1 , wherein the ratio of particles having a particle diameter of not more than 100 μm in the pellet is less than 20% by weight.
4. The granules according to claim 1 or 2, wherein the span (d 90 -d 10 ) / d 50 It is 0.9 to 2.
0.
5. The pellets according to claim 1 or 2, wherein the tamped density of the pellets is 300 g / L to 600 g / L.
6. The granular material according to claim 1 or 2, characterized in that The pellets have a porosity of less than 77% as measured by mercury intrusion porosimetry.
7. A method for preparing a pellet according to any one of claims 1 to 6, comprising the following steps: a) compacting fumed silica having a water content of 0.1% to 10% by weight to obtain compacted silica fragments having a tamped density of at least 200 g / L; b) crushing the compacted silicon dioxide fragments obtained in step a) using a sieve with a mesh size of 1000 μm to 2000 μm, while separating crushed fragments with a size of not more than 2000 μm; c) separating fine particles from the crushed fragments having a size of not more than 2000 μm obtained in step b) using a sieve having a mesh size of 200 μm to 600 μm to obtain the granules; d) optionally using the fine particles separated in step c) having a particle size of not more than 600 μm in step a).
8. The method according to claim 7, characterized in that The method is carried out continuously.
9. The method according to claim 7 or 8, characterized in that In step a) of the process, fumed silica is used having a water content of 0.5% to 5.0% by weight.
10. A method according to claim 7 or 8, characterised in that The mesh size of the sieve used in step b) of the process is 1000 μm to 1500 μm.
11. The method according to claim 7 or 8, characterized in that The mesh size of the sieve used in step c) of the method is 400 to 600 μm.
12. The method according to claim 7 or 8, further comprising a step e), wherein the pellets obtained in step c) of the method are exposed to an atmosphere containing one or more reactive compounds selected from: chlorine, hydrochloric acid, sulfur halides, sulfur oxyhalides, hydrogen, or mixtures thereof at a temperature of 400°C to 1100°C.
13. The method according to claim 7 or 8, wherein step a) of the method is performed by means of two compacting rollers, and the specific pressure applied between the two compacting rollers is greater than 12 kN / cm.
14. Use of the granules according to any one of claims 1 to 6 as catalyst carriers, carriers for liquid substances, in cosmetic applications, for thermal insulation, as pharmaceutical excipients, in the preparation of heat-treated silica granules, as abrasives, as components of silicone rubber.
15. Use of the granulate according to claim 14 in the preparation of heat-treated silicon dioxide granules at a temperature of at least 500°C.
Citation Information
Patent Citations
Sintered silicon dioxide materials
EP1717202A1
Granular functionalized silica, process for preparation thereof and use thereof
US20160082415A1
Synthetic amorphous silica powder and process for manufacturing same
US20170008772A1
Transmitter outage detection
US20190053150A1
Preparation of a quartz glass body in a multi-chamber oven
US20190062193A1
